In-situ synchrotron X-ray diffraction study of dual-step strain variation in laser shock peened metallic glasses. (May 2018) - Wang, Liang; Zhao, Yakai; Wang, Lu; Nie, Zhihua; Wang, Benpeng; Xue, Yunfei; Zhang, Haifeng; Fu, Huameng; Brown, Dennis E.; Ren, Yang
Abstract: Atomic-structure evolution is significant in understanding the deformation mechanism of metallic glasses. Here, we firstly find a dual-step atomic strain variation in laser-shock-peened (LSPed) metallic glasses during compression tests by using in-situ synchrotron X-ray diffraction. Under low compressive load, LSP-deformed zone's atomic-structure shows low Young's Modulus ( E ); with load increase, atomic-structure are re-hardened, showing high E . An atomic deformation mechanism is proposed by using flow unit model, that LSP could induce interconnected flow units and homogenize the atomic-structure. These interconnected flow units are metastable and start to annihilate during compressive loading, causing the dual-step atomic strain variation. Graphical abstract: Unlabelled Image